1994
DOI: 10.1080/03079459408419038
|View full text |Cite
|
Sign up to set email alerts
|

Brain lesions in young broiler chickens naturally infected with a mesogenic strain of Newcastle disease virus

Abstract: SUMMARYThirty-nine 4-to 5-week-old broiler chickens from an outbreak of Newcastle disease (ND) in Japan were examined pathologically. The causative agent was identified as a mesogenic strain of ND virus. Predominant gross lesions included haemorrhage in the lungs, congestion of the trachea, splenomegaly, atrophy of the thymus and bursa of Fabricius, and whitish discolouration of the brain. Microscopically, there was mild haemorrhagic pneumonia, catarrhal tracheitis, lymphoid necrosis in the spleen, thymus, bur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
15
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 21 publications
(25 reference statements)
4
15
0
Order By: Relevance
“…In this study, AIV coinfection was ruled out by testing the chicken and the propagated virus stock by using a rapid test and an HI test, respectively. A mixed infection with infectious bursal disease virus (IBDV) has been previously reported in a field ND case [4]. Co-infection of IBDV was also ruled out by direct RT-PCR using bursal RNA and IBDV-specific primers (data not shown).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, AIV coinfection was ruled out by testing the chicken and the propagated virus stock by using a rapid test and an HI test, respectively. A mixed infection with infectious bursal disease virus (IBDV) has been previously reported in a field ND case [4]. Co-infection of IBDV was also ruled out by direct RT-PCR using bursal RNA and IBDV-specific primers (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…, Nyoman Mantik ASTAWA 2) , Ketut Santhia Adhy PUTRA 3) , Yoshihiro HAYASHI 4) and Yasunobu MATSUMOTO 4) * 1) Pathology Laboratory and 2) The Newcastle disease virus (NDV) is an enveloped virus of paramyxoviridae with a negative-sense, single-stranded, nonsegmented RNA genome. NDVs cause the highly contagious and fatal Newcastle disease (ND) in almost all bird species.…”
mentioning
confidence: 99%
“…Generally, histologic lesions of the central nervous system are found in the cerebellum, medulla, midbrain, and spinal cord but rarely found in the cerebrum. 1 However, Bhaiyat et al 2 reported that the lesions were most frequently observed in the cerebrum in the broilers naturally infected with ND. The lesions of the present case were seen in the medulla, cerebrum, and cerebellum in decreasing order of frequency.…”
Section: Third Outbreakmentioning
confidence: 99%
“…Bhaiyat et al 2 reported nonpurulent encephalitis with malacia and pancreatic necrosis in the broilers naturally infected with mesogenic ND virus and IBD virus. The broilers had been vaccinated with ND vaccine.…”
Section: Third Outbreakmentioning
confidence: 99%
See 1 more Smart Citation